Misalignment Between Business and Information Technology(IT) Strategies: Risks Implication for Johannesburg Stock Exchange Listed Companies - Mantey, Nicholas Otu (Advances in Social Sciences Research Journal, 2022)
This article examines some aspect of Information Technology (IT) Governance and highlights potential risks companies can possibly encounter as a result of misalignment between business and IT strategies. Using a five point- likert scale questionnaire and a convenient sampling technique, data was collected online from fifty Chief Information Officers (CIO’s) operating on the Johannesburg Stock Exchange (JSE). The significance of this study can be viewed from two stand points- managerial and academic. From managerial standpoint this study examines the impactful consequences of misalignment of Business and IT strategies. From academic standpoint this study provides cognitive information for advancement of knowledge in the field of IT Governance research. The findings of this study revealed that from managerial standpoint there were various risks consequences associated with misalignment between business and IT strategies, ranging from management risks, operational dysfunctional of business processes, information security risks, financial risks, and reputational risks to companies.